Multilingual international students’ perceptions of support services from an identity perspective (Comparative & International Education Series, 2021)
Little has been discussed about the perspectives of multilingual international students toward support services from a student identity stance. This proposed chapter presents narrative accounts of four multilingual international students’ evolving interactions with support services at a university in Toronto, Canada, as the students worked to progressively construct and enact their real and hoped-for identities over time. By drawing on interviews and a critical approach to identity, this chapter seeks to demonstrate that, while support services tend to approach multilingual international students on the basis of skills needed for socio-academic success, in this study, the students approached support services on the basis of the potential contribution of support services to the construction of their multiple, but often neglected, identities, which the students felt were sometimes obscured by the institutional labels of “international” or “ESL” student.